2018
DOI: 10.1016/j.lwt.2017.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the freshness of fresh-cut green bell pepper (Capsicum annuum var. grossum) using electronic nose

Abstract: This study investigated a freshness assessment method utilizing electronic nose (e-nose) for fresh-cut green bell pepper (Capsicum annuum var. grossum) stored at 7±1 °C. Physicochemical results showed that the fresh-cut green bell peppers were fresh until 5 days and became spoiled at 7 days, particularly as evidenced by a surge in aerobic plate count and MDA content on subsequent days. The e-nose data combined hierarchical cluster analysis (HCA) can preliminarily distinguish between fresh (days 0, 1, 3 and 5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 39 publications
(31 reference statements)
0
33
0
Order By: Relevance
“…As shown in the radar diagram, the samples had high signals in sensors S1, S5, S6, S7, S9, and S13. These sensors represented aromatic compounds, alcohols, sulfur organic compounds, aliphatic hydrocarbons, and polar aromatic compounds, respectively (Chen, Zhang, Bhandari, & Guo, 2018; Sun, Zhang, Bhandari, & Yang, 2019; Wang, Zhang, Wang, & Martynenko, 2018). This was consistent with the GC–MS data of steamed stuffed bun in the research of Zhou and Yang (2016) that is, the main flavor substances included alcohols, hydrocarbons, aldehydes, aromatic compounds, sulfur compounds, heterocyclic compounds, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the radar diagram, the samples had high signals in sensors S1, S5, S6, S7, S9, and S13. These sensors represented aromatic compounds, alcohols, sulfur organic compounds, aliphatic hydrocarbons, and polar aromatic compounds, respectively (Chen, Zhang, Bhandari, & Guo, 2018; Sun, Zhang, Bhandari, & Yang, 2019; Wang, Zhang, Wang, & Martynenko, 2018). This was consistent with the GC–MS data of steamed stuffed bun in the research of Zhou and Yang (2016) that is, the main flavor substances included alcohols, hydrocarbons, aldehydes, aromatic compounds, sulfur compounds, heterocyclic compounds, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The ginger samples of different drying group (2.0 g dry basis) were placed in a sealed vial (20 mL) for 60min. The 14 sensors of the electronic nose (iNose; Ruifen Trading Co., Shanghai, China) were used to collect the aroma of each sample and the parameters of the electronic nose were selected based on the machine and the pre-experiment (Chen et al, 2018). The decline trend of the electronic nose aroma curve was very gentle after 150 s. Therefore, the acquisition time was setted at 150 s, which was enough to make the sensor stable.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The 14 sensors of the electronic nose represented 14 kinds of flavor substances, as shown in Table 1 (Chen et al, 2018). A radar diagram (Fig.…”
Section: Analysis Of Changes Of Volatile Components Using E-nosementioning
confidence: 99%
“…The hierarchical cluster analysis (HCA) showed the best separation between fresh and spoiled vegetables. Additionally, good correlation was achieved when aerobic plate count was quantified with PLS (R 2 = 0.9783, RMSE = 0.3317) [ 197 ]. The same group of authors reported good results when monitoring fresh-cut broccoli during storage with both SPME-GC–MS and electronic nose (14 MOS gas sensors).…”
Section: Electronic Nose: Historical Background and Food Quality Amentioning
confidence: 99%